Water-soluble exudates from seeds of Kochia scoparia exhibit antifungal activity against Colletotrichum graminicola - Houlihan, Adam J. (PLoS One, 2019)
Plant seed exudates are composed of complex mixtures of chemicals with potential for bioactive compounds with antimicrobial properties. This study focused on kochia (Kochia scoparia), one of many weedy plant species considered invasive in many agricultural systems. Extraction of compounds in water yielded an exudate mass equivalent to 7% of the original seed mass used. Water-soluble exudates were tested against 16 known plant pathogens in disk diffusion assays and kochia exudates were found to inhibit Colletotrichum graminicola, the fungal causative agent of anthracnose and stalk rot in maize. The narrow range of fungi found as targets suggested the mechanism of inhibition may be specific rather than broadly antifungal. A decline in viability of cells over four orders of magnitude occurred within six hours of exposure to exudate. The minimum inhibitory concentration was 3.125 mg L(-1). Hyphae formation in C. graminicola appeared inhibited following exposure to the exudate. Small molecular weight compounds as determined by GC/MS analysis showed high relative amounts of the sugars fructose, galactopyranose, glucose, and sorbitol, along with moderate proportions of organic acids and amino acids. Protein content averaged 0.7% in the standard concentration (100 mg mL(-1)) used for inhibition assays. Size fractionation of the exudate and subsequent disk diffusion assays revealed bioactive fractions with compounds in the MW range <5 kDa. To the best of our knowledge, this study is the first to show promising bioactivity against C. graminicola that was associated with water-extractable compounds from a common weed species. The results suggest that seeds of persistent plant species with long-lived seed banks like kochia may have potential for use in the discovery of compounds active in inhibiting fungal pathogens.